Analisis Kestabilan Model Penyebaran Penyakit Antraks pada Populasi Ternak dengan Transmisi Tak Langsung dan Penggunaan Desinfektan - Nur, Wahyudin; Renggawati, Rini; Dayasin; Nurfasilah; Alam, Syaherna; Yanti, Rista; Darmawati (Program Studi Matematika Universitas Sulawesi Barat, 2024)
Anthrax is an infectious disease caused by the bacterium Bacillus anthracis. This disease causes a fairly high mortality rate in livestock populations that can threaten food security in a region. Therefore, it is necessary to prevent and control its spread. This study aims to examine the model of the spread of anthrax disease in a livestock population by considering indirect transmission and the use of disinfectants. The constructed model is expressed as a system of ordinary differential equations. Dynamical analysis is carried out to identify the stability properties of the disease-free equilibrium point. The results of the dynamical analysis show that the disease-free equilibrium point is conditionally stable, namely when the basic reproduction number is less than one. In addition, the results of numerical experiments show that the use of disinfectants has a significant effect on the dynamics of the spread of anthrax disease, namely the higher the rate of bacterial death due to disinfectants, the fewer cases of anthrax. This study shows that the use of disinfectants can be an effective strategy to control the spread of anthrax disease in livestock populations.